(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2023)
The article clarifies the features of the artistic interpretation of the concept of “death” in the novel “The Servant from Dobromil”, the specifics of its individual and authorial linguistic objectification are revealed. The concept is characterized through the prism of a special internal organization, which is formed on the basis of the corresponding concept. The basis of this concept is the set of lexical meanings of the word “death”. The studied concept is considered within the framework of binary opposition. Attention is focused on the value guidelines of the national culture formed over many centuries, which are supplemented by the writer’s aesthetic views, ideals, and moral and ethical preferences. This expands the spectrum of ideas about death, makes it possible to build new semantic paradigms. The modified semantic content of the corresponding concept, the original individual-author worldview, and unexpected associative connections are considered. The religious and idealistic views that recognize the existence of supernatural forces and the possibility of human communication with them are updated. The individual author’s picture of the world is presented in a mystical plane. A number of verbal means that either directly or indirectly explicate the concept of “death” are outlined. Emphasis is placed on various spreaders, which are epithet characteristics, stereotypical verbal markers, perform the function of agreed or disagreed meanings. The syntagmatic dimension of the semantic space of the concept is presented: the peculiarities of the functioning of the lexeme “death” in the composition of free phrases, phraseological and metaphorical constructions are established. The word-forming dimension of the semantic space of the concept “death” related to adjectival and adverbial derivatives is outlined.